Grundtvigs skoletanker i Filippinerne - Zøllner, Lilian (Grundtvig-Studier, 1994)
Grundtvig’s Educational Ideas in the Philippines By Lilian Zøllner In 1991 an initiative was taken to establish a folk high school in the Philippines, based upon Grundtvig’s educational ideas. The project was supported financially by Folkekirkens Nødhjælp (Danchurchaid) and Danida. The establishment of the folk high school was the work of the former Catholic priest, Edicio dela Torre, who was arrested on December 13th, 1974, by the Marcos regime and accused of being one of the leaders of the NDF (the National Democratic Front). On March 1st, 1986, he was released and left the Philippines. In 1991 Edicio dela Torre was invited to give lectures at Danish folk high schools. These meetings resulted in Edicio dela Torre having a vision of setting up a folk high school in the Philippines, where the education was to for life, viz life in the local communities which was fundamental to the work and importance of the grassroots leaders. The folk high school faces great challenges: to overcome earlier experiences with the educational system, to convince the population, to find a place in the non-formal educational offers, to keep the well-educated people in the country, and to cooperate in spite of political and religious differences.